Generalized Relative Type and Generalized Weak Type of Entire Functions. (13th July 2016) - Datta, Sanjib Kumar; Biswas, Tanmay; Dutta, Debasmita
Abstract : We study some relative growth properties of entire functions with respect to another entire function on the basis of generalized relative type and generalized relative weak type.